Effects of Cold Stress on the Hemolymph of the Pacific White Shrimp Penaeus vannamei - Jianqiang Zhu; Wenjun Shi; Ran Zhao; Chen Gu; Hui Li; Libao Wang; Xihe Wan (Fishes, 2024)
Temperature is an important factor in the physiological processes of aquatic organisms and can seriously affect several chemical and biological processes in their bodies, including respiratory metabolism, antioxidant capacity, immune capacity, and signal transduction. In this study, physiological, transcriptomic, and metabolomic analyses were used to investigate the response of Penaeus vannamei to cold stress. The results indicated that cold stress disrupted nucleotide metabolism and inhibited gluconeogenesis. However, shrimp exhibited response mechanisms in order to enhance cold tolerance, regulating changes in key genes and metabolites in amino acid and lipid metabolism to increase energy supply and protect cell membrane stability. In addition, the response included regulating Ca2+ pumps and ion channels to maintain intracellular ion homeostasis and osmotic balance. When the temperature dropped further, oxidative damage occurred due to overwhelming of the antioxidant defense system, and immune function was inhibited. This research provides some references regarding the molecular mechanisms involved in responding to cold stress and potential strategies to improve cold tolerance in P. vannamei; these are important references for studying the cold stress response of shrimp.